2013
DOI: 10.1364/oe.21.000918
|View full text |Cite
|
Sign up to set email alerts
|

Scanning near-field optical coherent anti-Stokes Raman microscopy (SNOM-CARS) with femtosecond laser pulses in vibrational and electronic resonance

Abstract: Accessing ultrafast photoinduced molecular dynamics on a femtosecond time-scale with vibrational selectivity and at the same time sub-diffraction limited spatial resolution would help to gain important information about ultrafast processes in nanostructures. While nonlinear Raman techniques have been used to obtain highly resolved images in combination with near-field microscopy, the use of femtosecond laser pulses in electronic resonance still constitutes a big challenge. Here, we present our first results on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(14 citation statements)
references
References 29 publications
0
14
0
Order By: Relevance
“…Unauthenticated Download Date | 5/12/18 6:19 AM electronic and vibrational resonance is capable of yielding highly resolved images of P3HT in different environments [14]. It has to be pointed out, that the goal of our work was not to improve existing CARS imaging techniques, but rather to make an important step towards a timeresolved application in the near-field.…”
Section: Scanning Near-field Cars (Snom-cars)mentioning
confidence: 99%
See 3 more Smart Citations
“…Unauthenticated Download Date | 5/12/18 6:19 AM electronic and vibrational resonance is capable of yielding highly resolved images of P3HT in different environments [14]. It has to be pointed out, that the goal of our work was not to improve existing CARS imaging techniques, but rather to make an important step towards a timeresolved application in the near-field.…”
Section: Scanning Near-field Cars (Snom-cars)mentioning
confidence: 99%
“…[14]) was calculated using WSXM software developed by Horcas et al [31]; it is shown in Figure 7C. In order to guarantee that the AFM topography matches the SNOM image as precisely as possible, the images were recorded using a SNOM tip having an aperture of ≈200-300 nm and a metal coating of 0.2 μm thickness.…”
Section: Scanning Near-field Cars (Snom-cars)mentioning
confidence: 99%
See 2 more Smart Citations
“…Scanning near‐field optical microscopy (SNOM) has proved to be a powerful tool to achieve sub‐wavelength resolution in both imaging and fabrication7a,8 of a variety of nanostructures, in particular for its capabilities in obtaining simultaneous topographical and photoluminescence images7b,9—and often further information such as the local photoconductivity, polarization,1a,11 surface plasmons, mechanical stress, Raman signal,13b,14 thickness, dichroism or the chemical composition of the sample. As with other members of the scanning probe family of techniques, SNOM is primarily aimed at surface characterization, although the nature of the evanescent optical field allows a degree of sub‐surface probing.…”
Section: Introductionmentioning
confidence: 99%